Phytohormonal Regulation Through Protein S-Nitrosylation Under Stress - Pande, Anjali; Mun, Bong Gyu; Rahim, Waqas; Khan, Murtaza; Lee, Da Sol; Lee, Geun Mo; Al Azzawi, Tiba Nazar Ibrahim; Hussain, Adil; Kim, Chang Kil; Yun, Byung Wook (Frontiers in Plant Science, 2022)
The liaison between Nitric oxide (NO) and phytohormones regulates a myriad of physiological processes at the cellular level. The interaction between NO and phytohormones is mainly influenced by NO-mediated post-translational modifications (PTMs) under basal as well as induced conditions. Protein S-nitrosylation is the most prominent and widely studied PTM among others. It is the selective but reversible redox-based covalent addition of a NO moiety to the sulfhydryl group of cysteine (Cys) molecule(s) on a target protein to form S-nitrosothiols. This process may involve either direct S-nitrosylation or indirect S-nitrosylation followed by transfer of NO group from one thiol to another (transnitrosylation). During S-nitrosylation, NO can directly target Cys residue (s) of key genes involved in hormone signaling thereby regulating their function. The phytohormones regulated by NO in this manner includes abscisic acid, auxin, gibberellic acid, cytokinin, ethylene, salicylic acid, jasmonic acid, brassinosteroid, and strigolactone during various metabolic and physiological conditions and environmental stress responses. S-nitrosylation of key proteins involved in the phytohormonal network occurs during their synthesis, degradation, or signaling roles depending upon the response required to maintain cellular homeostasis. This review presents the interaction between NO and phytohormones and the role of the canonical NO-mediated post-translational modification particularly, S-nitrosylation of key proteins involved in the phytohormonal networks under biotic and abiotic stresses.